CD4/CD8 Ratio as a Novel Marker for Increased Risk of High-Grade Anal Dysplasia and Anal Cancer in HIV+ Patients: A Retrospective Cohort Study. Issue 12 (December 2020) - Geltzeiler, Cristina B.; Xu, Yiwei; Carchman, Evie; Ghouse, Youhi; Beczkiewicz, Jeffrey; Son, Joohee; Voils, Corrine I.; Striker, Rob
Abstract : BACKGROUND: People living with HIV are at risk for anal dysplasia/cancer. Screening/surveillance is costly and burdensome, and the frequency is not evidence based. Objective markers of increased risk of anal carcinogenesis are needed to tailor screening/surveillance. Low CD4/CD8 ratio is associated with increased overall cancer risk in people living with HIV but has yet to be examined for quantifying anal cancer risk. OBJECTIVE: We hypothesized that low CD4/CD8 ratios correlate with increased risk for high-grade anal dysplasia and cancer. DESIGN: This is a single-institution, retrospective review of people living with HIV from 2002 to 2018. SETTING: This study was conducted at the University of Wisconsin School of Medicine and Public Health. PATIENTS: Patients with advanced disease (high-grade anal dysplasia and/or anal cancer) were compared with patients with negative anal cytology. MAIN OUTCOME MEASURES: The independent variables were lowest (nadir) CD4/CD8 and CD4/CD8 nearest to screening/diagnosis. Logistic regression modeling was used to estimate the adjusted odds of advanced disease. RESULTS: A total of 377 people living with HIV were examined: 266 with negative cytology and 111 with advanced disease (16 cancer, 95 high-grade anal dysplasia). Mean nadir ratio and mean nearest ratio were lower in patients with advanced disease than in those with negative screening (0.26 vs 0.47 ( p < 0.001) and 0.61 vs 0.87 ( p < 0.001)). In adjusted analyses, increase in nadir ratio or nearest ratio of 1 unit conferred decreased risk of advanced disease (OR, 0.10; 95% CI, 0.02–0.45; p = 0.002) and (OR, 0.31; 95% CI, 0.12–0.83; p = 0.02). The optimal threshold for using CD4/CD8 ratio as a risk factor for advanced disease was 0.47 for nadir ratio (sensitivity 0.59 and specificity 0.91) and 0.95 for nearest ratio (sensitivity 0.56 and specificity 0.92). LIMITATIONS: This is a retrospective, single-institution study. CONCLUSIONS: Low CD4/CD8 ratio confers additional risk of high-grade anal dysplasia and anal cancer beyond the diagnosis of HIV, even when adjusting for known risks factors of anal cancer. Our data suggest that the CD4/CD8 ratio may be able to help identify people living with HIV who are at higher risk of anal cancer development. See Video Abstract at http://links.lww.com/DCR/B336 . LA RELACIÓN CD4 / CD8 COMO UN MARCADOR NOVEDOSO PARA EL AUMENTO DEL RIESGO DE DISPLASIA ANAL DE ALTO GRADO Y CÁNCER ANAL EN PACIENTES VIH+: UN ESTUDIO DE COHORTE RETROSPECTIVO: ANTECEDENTES: Las personas que viven con el virus de la inmunodeficiencia humana están en riesgo de displasia / cáncer anal. La detección / vigilancia es costosa, laboriosa y la frecuencia no se basa en evidencias. Se necesitan marcadores objetivos de mayor riesgo de carcinogénesis anal para adaptar la detección / vigilancia. La relación baja de CD4 / CD8 se asocia con un mayor riesgo general de cáncer en personas que viven con el virus de inmunodeficiencia humana, pero aún no se ha examinado para cuantificar el riesgo de cáncer anal. OBJETIVO: Hicimos la hipotesis de que la relación baja de CD4 / CD8 se correlacionan con un mayor riesgo de displasia anal de alto grado y cáncer. DISEÑO: Revisión retrospectiva de una sola institución de personas que viven con el virus de la inmunodeficiencia humana desde 2002 hasta 2018. AJUSTE: Facultad de Medicina y Salud Pública de la Universidad de Wisconsin. PACIENTES: Los pacientes con enfermedad avanzada (displasia anal de alto grado y / o cáncer anal) se compararon con pacientes con citología anal negativa. PRINCIPALES MEDIDAS DE RESULTADO: Las variables independientes más bajas fueron (nadir) CD4 / CD8 y la relación CD4 / CD8 más cercanas a la detección / diagnóstico. Se utilizó el modelo de regresión logística para estimar las probabilidades ajustadas de enfermedad avanzada. RESULTADOS: Se examinaron un total de 377 personas que viven con el virus de inmunodeficiencia humana, 266 con citología negativa y 111 con enfermedad avanzada (16 cáncer, 95 displasia anal de alto grado). La tasa nadir y la tasa media más cercana fueron más bajas en pacientes con enfermedad avanzada vs. aquellos con cribado negativo (0.26 v. 0.47 ( p <0.001) y 0.61 v. 0.87 ( p <0.001), respectivamente. En los análisis ajustados, el aumento en la tasa nadir o la tasa más cercana a una unidad confirió una disminución del riesgo de enfermedad avanzada (OR de 0, 10 (IC del 95%: 0, 02, 0, 45, p = 0, 002)) y (OR 0, 31 (IC del 95%: 0, 12, 0, 83, p = 0.02)), respectivamente. El umbral óptimo para usar la relacion CD4 / CD8 como factor de riesgo de enfermedad avanzada fue 0, 47 para la tasa nadir (sensibilidad 0, 59 y especificidad 0, 91) y 0, 95 para la tasa más cercana (sensibilidad 0, 56 y especificidad 0, 92). LIMITACIONES: Este es un estudio retrospectivo de una sola institución. CONCLUSIONES: La baja relación CD4 / CD8 confiere un riesgo adicional de displasia anal de alto grado y cáncer anal más allá del diagnóstico del virus de inmunodeficiencia humana, incluso cuando se ajustan los factores de riesgo conocidos de cáncer anal. Nuestros datos sugieren que la relación CD4/CD8 puede ayudar a identificar a las personas que viven con el virus de inmunodeficiencia humana que tienen un mayor riesgo de desarrollar cáncer anal. Consulte Video Resumen en http://links.lww.com/DCR/B336 . Abstract : Supplemental Digital Content is available in the text.